Credit Risk Management Practices of Indian Banking Industry: An Empirical Study - Brahmaiah, Bezawada (International Journal of Economics and Financial Issues, 2022)
The primary objective of this paper is to examine the risk management techniques and practices of credit risk management followed by Indian commercial banks for the period from 2021-17 to 2020-21. The other objective is to compare risk management practices followed by the public sector banks (PSBs) and private sector of banks (PVBs). The study uses a sample of twelve banks consisting of six largest public sector banks (PSBs) and six largest private sector banks (PVBs) for the study. The sample accounts for 78 per cent of the banking business of the country. The study finds that the scheduled commercial banks (SCBs) are facing credit risk, market risk and operational risk. The study finds that the credit risk management process and practices include risk identification, risk assessment, risk analysis, risk evaluation, risk monitoring and risk control. The study finds that private sector banks (PVBs) have better credit risk management practices as compared to that of public sector banks (PSBs). The PSBs have more NPAs than PVBs whereas PVBs have better asset quality and better profitability ratios than PSBs during the study period.